Follow-up interval for small untreated pulmonary arteriovenous malformations in hereditary haemorrhagic telangiectasia. Issue 3 (March 2017) - Ryan, D.J.; O'Connor, T.M.; Murphy, M.M.; Brady, A.P.
Abstract : Aim: To investigate the natural history of untreated small (<3 mm) and microscopic pulmonary arteriovenous malformations (PAVMs) in hereditary haemorrhagic telangiectasia (HHT) in order to discern the optimal frequency of follow-up thoracic computed tomography (CT). Materials and methods: A retrospective analysis was performed on the follow-up data for definite and suspected HHT patients with untreated PAVMs. Results: For small PAVMs in definite HHT ( n =13), PAVM enlargement was identified in one patient (1/13, 7.7%) after 10.7 years follow-up and was successfully treated using transcatheter embolisation (TCE). For microscopic PAVMs in definite HHT ( n =28), two patients (2/28, 7%) developed small asymptomatic PAVMs, which did not meet the size criteria for TCE after 6.8 years of follow-up. For small PAVMs in suspected HHT ( n =5), feeding artery enlargement was seen in one patient (1/5, 20%) after 7.9 years, but again, this did not meet the size criteria for embolisation. No macroscopic PAVM development was identified after a median follow-up of 5.4 years in suspected HHT with microscopic PAVMs ( n =20). Conclusion: For small and microscopic PAVMs in HHT, PAVM enlargement was found to be more infrequent than would be expected based on current guidelines; therefore, potentially challenging the current surveillance imaging recommendation of a repeat thoracic CT every 5 years. Highlights: At present the optimal frequency of follow-up imaging in <3 mm PAVMs in HHT is unknown. We investigated the natural history of untreated small and microscopic PAVMs in HHT at our institution. PAVM enlargement was found to be more infrequent than would be expected based on current guidelines. Our findings potentially challenge the current recommendation of a repeat thoracic CT every 3 - 5 years.